PERSEPSI BIAS GENDER DALAM PRODUKSI FILM: STUDI TERHADAP ANGGOTA PEREMPUAN EKSTRAKURIKULER 3SINEMA - Muhammad Bintang Mahardika Wirasatria; Ade kusuma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
SMKN 3 Surabaya has an imbalanced gender composition (82% male), which potentially shapes a masculine culture affecting the dynamics of the 3Sinema film production extracurricular. This study aims to explore female members perception of gender bias in film production activities, using a descriptive qualitative approach through in-depth interviews with five female informants selected via purposive sampling. Data were analyzed using Qiong (2017) theory of perception (selection, organization, interpretation) and linked to the concepts of gender bias. Findings show that female members recognize gender bias through direct experience, though their conceptual understanding varies. Gender bias appears as stereotypes attaching administrative roles (scriptwriter, assistant director) to women and technical roles (cameraman, gaffer) to men; limited female authority in creative decision-making, with women positioning themselves as idea executors rather than decision-makers; and verbal jokes that subtly perpetuate women's inferior position. The study concludes that female members' perception of gender bias is conscious yet felt emotionally but rarely openly resisted due to its subtle forms, thereby also affecting group communication effectiveness at 3Sinema.